Pengendalian Pemekaran Fisik Kota: Belajar Dari Pengalaman Kota Lexington-Fayette (Kentucky, A.S.) Dan Kota-kota Kecil Di Sekitarnya - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Biologi UGM, 2000)
This study focuses on the application of theories or concepts for managing urban physical growth applied to Lexington-Fayette, Kentucky and its surrounding towns. Two theories/concepts were employed by the city and towns i.e. Garden City of Tomorrow by Ebenezer Howard in 1902 and Urban Growth Boundaries. Efforts in managing the urban growth were supported by the whole community, especially the farm house owners. The farms became the green belt areas preventing the urban areas from expanding toward urban sprawl. Considering for applying this concept to Indonesian cities. it seems that for the time being, Indonesian local governments do not see the problem as their major issue. However, as the new Local Autonomy Act implemented in the future, there may be "rich" local governments in Indonesia who will be able to buy agriculture land and conserve them as barriers for urban expansion. Hopefully, urban sprawl may be prevented from happening in Indonesian major cities.